Variations of Indian monsoon precipitation during the last 32 kyr reflected in the surface hydrography of the Western Bay of Bengal - Govil, P.; Naidu, P.D. (Elsevier, 2011)
Hydrography of the Bay of Bengal is highly influenced by the river runoff and rainfall during the southwest monsoon. We have reconstructed delta sup(18)Osw, sea surface salinity and sea surface temperature (SST) changes in the Bay of Bengal by using paired measurements of delta sup(18)O and Mg/Ca in a planktonic foraminifera species Globigerinoides ruber from core SK218/1 in the western Bay of Bengal in order to understand the rainfall variability associated with southwest monsoon over the past 32 kyr. Our SST reconstructions reveal that Bay of Bengal was approx 3.2 degrees C cooler during the LGM as compared to present day temperature and a approx 3.5 degrees C rise in SST is documented from 17 to 10 ka. Both SST and delta sup(18)Osw exhibit greater amplitude fluctuations during MIS 2 which is attributable to the variability of NE monsoon rainfall and associated river discharge into the Bay of Bengal in association with strong seasonal temperature contrast. On set of strengthening phase of SW monsoon was started during Bolling/Allerod as evidenced by the low delta sup(18)Osw values approx 14.7 ka. delta sup(18)Osw show consistently lower values during Holocene (with an exception around 5 ka), which suggests that the freshening of Bay of Bengal due to heavy precipitation and river discharge caused by strong SW monsoon. Results of this study signify that the maximum fluctuations of the NE monsoon rainfall during MIS 2 appear to be controlled by the strong seasonality and boundary conditions.